Microfiber spinning oil and preparation method thereof
Through the combination of nano-titanium dioxide modified polyurethane resin and polyol, combined with modified fillers and zwitterionic surfactants, the compatibility and stability of the spinning oil agent are solved, the weather resistance and fracture strength of the fiber are improved, and the high temperature is achieved. Performance of spinning oil agent preparation.
Patent Information
- Application Number
- CN202411670807.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-01-03
AI Technical Summary
When existing spinning oil agents are used to make high-simulation, high-value added artificial suede, there are problems in compatibility, dispersion, balance of strength and softness, durability, etc., resulting in poor spinning process. , poor performance and poor storage stability.
Nanotitanium dioxide pioneer liquid is used to prepare nanotitanium dioxide modified polyurethane resin, combined with a variety of polyether polyol compounding, modified fillers and specific proportions of zwitterionic surfactants to form a stable composite network structure and improve fiber Weather resistance and fracture strength, and ultrasonic dispersion technology are used to prepare ultrasonic spinning oil agent.
It significantly improves the weather resistance, mechanical properties and storage stability of spinning oil agents, ensures the high performance and durability of fibers, and is suitable for the processing of high-simulation, high value-added artificial suede.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of textiles, and in particular relates to a microfiber spinning oil and a preparation method thereof. Background Art
[0002] Spinning oil is an auxiliary agent widely used in the textile industry. It is mainly used for lubrication and anti-static of chemical fibers or synthetic fibers during the spinning process, thereby ensuring the various processing properties of the fibers. Ultrafine fibers are one of the main types of differentiated fibers. In order to ensure good spinnability, stretchability and post-processing performance, in addition to appropriate fiber processing conditions, special spinning or post-processing oils are also required. In particular, when using ultrafine fibers to manufacture highly simulated, high value-added artificial suede, spinning oils with high anti-static and high lubrication properties are required, which have a crucial impact on the processing of nonwoven fabrics and the quality of artificial suede.
[0003] When used in ultrafine fiber manufacturing of high-simulation, high-value-added artificial suede, spinning oil may encounter some technical problems. For example: (1) Compatibility issues: Poor compatibility between the oil and the fiber matrix may result in the oil being unable to be evenly distributed on the fiber surface, thereby affecting the fiber performance. (2) Dispersion issues: The oil may be difficult to evenly disperse on the fiber surface, especially in the case of ultrafine fibers, which may increase the friction between the fibers and affect the smoothness of the spinning process. (3) Balance between strength and softness: Artificial suede needs to have good strength and softness, which places higher requirements on the oil. (4) The oil needs to be able to both improve the strength of the fiber and maintain good softness. (5) Durability: In order to improve the durability of artificial suede, the oil needs to be able to resist washing and wear while maintaining the original performance of the fiber. In the prior art, the formula is usually optimized and an appropriate dispersant is added to help the oil be better dispersed on the fiber surface and reduce agglomeration, but this often leads to poor storage stability of the spinning oil and cannot meet the needs of the existing market.
[0004] Therefore, there is an urgent need for a microfiber spinning oil and a preparation method thereof. Summary of the invention
[0005] The purpose of the present invention is to provide a superfiber spinning oil and a preparation method thereof.
[0006] In order to achieve the above object, the present invention provides the following technical solutions: A microfiber spinning oil, comprising the following components in parts by weight: 12-17 parts of castor oil, 3-8 parts of white oil, 25-30 parts of polyurethane resin, 1-3 parts of modified filler, 2-5 parts of antistatic agent, 6-10 parts of wetting agent, 4-8 parts of emulsifier, 1-3 parts of defoamer, 1-3 parts of leveling agent, 2-5 parts of dispersant, and 30-36 parts of deionized water; The preparation method of the polyurethane resin comprises the following steps: (1) adding a titanium tetrachloride aqueous solution to a benzoic acid aqueous solution in a volume ratio of 1:(4-6), stirring evenly, to obtain a nano-titanium dioxide precursor solution, wherein the molar concentrations of the titanium tetrachloride aqueous solution and the benzoic acid aqueous solution are both 0.2-0.5 mol / L; (2) Weigh 4-6 parts by weight of diisocyanate, 1 part by weight of polyether polyol, and 10-12 parts by weight of butanone, mix them evenly to obtain a mixed solution, add 5-10% by weight of nano-titanium dioxide precursor solution to the mixed solution, heat it to 75-80°C, keep it warm for 3-4 hours, continue to add 5-7 parts by weight of polyether polyol and 0.5-0.8 parts by weight of organic bismuth catalyst, react at 80-85°C for 4-6 hours, cool it to 40-45°C, continue to add 4-6 parts by weight of 1,4-butanediol, 2-4 parts by weight of triethylamine and 5-7 parts by weight of deionized water, mix them evenly, heat it to 72-76°C, keep it warm for 5-6 hours, and cool it to room temperature to obtain a polyurethane resin.
[0007] At present, modified titanium dioxide is usually added to polyurethane on the market to improve the weather resistance of spinning oil, but due to poor compatibility, it is often mixed unevenly, and the actual improvement effect is not ideal. The present invention adds nano titanium dioxide precursor liquid to the polyurethane reaction system for in-situ polymerization to obtain a nano titanium dioxide modified polyurethane material, which is conducive to the uniform dispersion of nano titanium dioxide particles in polyurethane and improves the weather resistance of spinning oil. However, it is found in the test process that the weather resistance of the spinning oil after washing is not ideal.
[0008] Furthermore, the polyether polyol is a compound of polyether polyol A, polyether polyol B and polyether polyol C in a mass ratio of (0.2-0.5):(1.3-1.5):1; wherein polyether polyol A is a polyether triol having a hydroxyl number of 535 mgKOH / g; polyether polyol B is a polyether diol having a hydroxyl number of 36-39 mgKOH / g; and polyether polyol C is a polyether diol having a hydroxyl number of 153-188KOH / g.
[0009] Polyether triol with hydroxyl number of 535 mgKOH / g, Arkema, France, model TO330. Polyether diol with hydroxyl number of 36-39 mgKOH / g, Xuzhou Yihuiyang New Materials Co., Ltd., DL-3000D. Polyether diol with hydroxyl number of 153-188KOH / g, Jining Tangyi Chemical Co., Ltd., HSH-310.
[0010] The present invention uses three different polyether polyols to be compounded in a specific ratio for preparing polyurethane, which can improve the weather resistance of the spinning oil after washing. Because the polyurethane prepared by the compounded polyether polyol has a complex network structure, a strong interface bonding is formed between the nano titanium dioxide and the polyurethane matrix, and a stable composite network structure is established, so that the titanium dioxide can be more firmly fixed in the polyurethane, and the water washing resistance and stability are stronger.
[0011] The organic bismuth catalyst was purchased from Shandong Xinghai Chemical Co., Ltd., model: organic bismuth catalyst LK-2.
[0012] Furthermore, the diisocyanate is selected from one or more of toluene diisocyanate, isophorone diisocyanate and hexamethylene diisocyanate.
[0013] Furthermore, the preparation method of the modified filler comprises the following steps: mixing carboxylated double-walled carbon nanotubes, carboxylated graphene oxide and carboxylated silicon dioxide in a mass ratio of 1: (0.3-0.6): (1.3-1.6) to obtain a filler; mixing 2-4 parts by mass of polyethyleneimine and 6-8 parts by mass of water under a nitrogen atmosphere to obtain a polyethyleneimine aqueous solution; mixing the polyethyleneimine aqueous solution and 1 part by mass of the filler, stirring at 60-65° C. for 8-10 hours, centrifuging, and drying to obtain a modified filler.
[0014] Furthermore, the carboxylated double-walled carbon nanotubes have a diameter of 2-4 nm, a length of 0.5-2 μm, and a carboxyl content of 2.58 wt %, and are purchased from Xianfeng Nano, item number: 100227.
[0015] Furthermore, the carboxylated graphene oxide sheet has a diameter of 0.5-5 micrometers and a thickness of 0.8-1.2 nm, and is purchased from Xianfeng Nano, item number: 100009.
[0016] Furthermore, the average size of carboxylated silica is 20 nm and is purchased from Xianfeng Nano, item number: 103113.
[0017] The present invention attempts to add fillers to improve the effect of the spinning oil on the breaking strength of the fiber, but the compatibility of the filler with other systems is not ideal. The present invention improves the effect of the spinning oil on the breaking strength of the fiber by modifying the filler. The amino group of polyethyleneimine reacts with the carboxyl group of the filler to graft the polyethyleneimine onto the filler. The modified filler has better compatibility with the system and has a better effect on improving the breaking strength of the fiber by the spinning oil. When the filler is compounded in a specific ratio, the elongation of the fiber by the spinning oil can be improved.
[0018] Furthermore, the wetting agent is a mixture of Tween 60, Span 80 and Tween 80 in a mass ratio of 1: (1.2-1.4): (1.5-1.7).
[0019] Furthermore, the emulsifier is a mixture of peregal O, sodium dodecylbenzene sulfonate and a zwitterionic surfactant in a mass ratio of 1: (0.3-0.6): (1.4-1.7).
[0020] Furthermore, the preparation method of the zwitterionic surfactant comprises the following steps: S1: dissolving 12-14 parts by weight of 4-amino-3-hydroxybenzoic acid and 20-23 parts by weight of epichlorohydrin in 55 parts by weight of ethanol, adding 4-6 parts by weight of a 0.2-0.4 mol / L aqueous solution of sodium hydroxide, heating to 80-85° C., reacting for 10-15 hours, and obtaining a product; S2: Mix the product, 50-55 parts by weight of hexadecyldimethyl tertiary amine, 80-85 parts by weight of ethanol and 70-75 parts by weight of water, heat to 80-85° C., react for 25-30 hours, and remove the ethanol by rotary evaporation to obtain a zwitterionic surfactant.
[0021] However, after the filler is added to the system of the present invention, the storage stability of the spinning oil is poor, and stratification is easy to occur after long-term storage. At the same time, the improvement effect of using commercially available products as emulsifiers is not ideal. The present invention uses the prepared zwitterionic surfactant and the specific proportion of pingpingjia O and sodium dodecylbenzene sulfonate to improve the stability of the spinning oil. Because under this condition, the emulsifier can significantly reduce the interfacial tension between the oil and water, making the oil easier to form a stable emulsion with water, which helps the particles to be more evenly dispersed in water to form a stable emulsion system.
[0022] Furthermore, the antistatic agent is selected from one or more of polyoxyethylene lauryl alcohol ester, sorbitol, and ethanolamide.
[0023] Furthermore, the defoaming agent is selected from one or more of TEGO901W defoaming agent, TEGO902W defoaming agent, TEGO801W defoaming agent and TEGO810W defoaming agent.
[0024] Furthermore, the leveling agent is selected from one or more of BYK300, BYK306 and BYK333.
[0025] Furthermore, the dispersant is selected from one or more of TEGODispers715w, TEGODispers755w, and TEGOWet280.
[0026] The present invention also provides a method for preparing a superfiber spinning oil, which comprises the following steps: adding modified filler, castor oil and white oil into a reactor, controlling the temperature of the reactor to be 35-38°C, ultrasonically dispersing for 15-20 minutes, adding the remaining components, and stirring for 20-30 minutes to obtain the superfiber spinning oil.
[0027] Compared with the prior art, the advantages and beneficial effects of the present invention are: 1. The ultrafine fiber spinning oil prepared by the present invention has good stability and will not delaminate or precipitate after being placed for a long time. The ultrafine fibers treated with the ultrafine fiber spinning oil prepared by the present invention have excellent weather resistance and mechanical properties and have broad application prospects.
[0028] 2. The present invention adds nano-titanium dioxide precursor solution into the polyurethane reaction system for in-situ polymerization to obtain nano-titanium dioxide modified polyurethane material, which is beneficial to the uniform dispersion of nano-titanium dioxide particles in polyurethane and improves the weather resistance of the spinning oil.
[0029] 3. The present invention uses three different polyether polyols to be compounded in a specific ratio for preparing polyurethane, which can improve the weather resistance of the spinning oil after washing.
[0030] 4. The present invention improves the effect of the spinning oil on the breaking strength of the fiber by modifying the filler. When the filler is compounded in a specific ratio, the elongation of the fiber by the spinning oil can be improved.
[0031] 5. The present invention uses the prepared zwitterionic surfactant and pyrochlore O and sodium dodecylbenzene sulfonate in a specific ratio to improve the stability of the spinning oil. DETAILED DESCRIPTION
[0032] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0033] Example 1 This embodiment provides a microfiber spinning oil, comprising the following components in parts by weight: 15 parts of castor oil, 5 parts of No. 5 white oil, 27 parts of polyurethane resin, 2 parts of modified filler, 4 parts of antistatic agent, 7 parts of wetting agent, 5 parts of emulsifier, 2 parts of defoamer, 2 parts of leveling agent, 4 parts of dispersant, and 35 parts of deionized water; The preparation method of the polyurethane resin comprises the following steps: (1) adding a titanium tetrachloride aqueous solution to a benzoic acid aqueous solution in a volume ratio of 1:5, stirring evenly, to obtain a nano-titanium dioxide precursor solution, wherein the molar concentrations of the titanium tetrachloride aqueous solution and the benzoic acid aqueous solution are both 0.3 mol / L; (2) Weigh 5 parts by mass of diisocyanate, 1 part by mass of polyether polyol, and 11 parts by mass of butanone, mix them evenly to obtain a mixed solution, add 7% by mass of nano-titanium dioxide precursor solution to the mixed solution, heat it to 78°C, keep it warm for 3.6 hours, continue to add 6 parts by mass of polyether polyol and 0.7 parts by mass of organic bismuth catalyst, react at 82°C for 5 hours, cool it to 42°C, continue to add 5 parts by mass of 1,4-butanediol, 3 parts by mass of triethylamine and 6 parts by mass of deionized water, mix them evenly, heat it to 74°C, keep it warm for 5.6 hours, and cool it to room temperature to obtain a polyurethane resin.
[0034] The polyether polyol is a compound of polyether polyol A, polyether polyol B and polyether polyol C in a mass ratio of 0.4:1.4:1; wherein polyether polyol A is a polyether triol with a hydroxyl number of 535 mgKOH / g; polyether polyol B is a polyether diol with a hydroxyl number of 36-39 mgKOH / g; and polyether polyol C is a polyether diol with a hydroxyl number of 153-188KOH / g.
[0035] Polyether triol with hydroxyl number of 535 mgKOH / g, Arkema, France, model TO330. Polyether diol with hydroxyl number of 36-39 mgKOH / g, Xuzhou Yihuiyang New Materials Co., Ltd., DL-3000D. Polyether diol with hydroxyl number of 153-188KOH / g, Jining Tangyi Chemical Co., Ltd., HSH-310.
[0036] The organic bismuth catalyst was purchased from Shandong Xinghai Chemical Co., Ltd., model: organic bismuth catalyst LK-2.
[0037] The diisocyanate is toluene diisocyanate.
[0038] The preparation method of the modified filler comprises the following steps: mixing carboxylated double-walled carbon nanotubes, carboxylated graphene oxide and carboxylated silicon dioxide in a mass ratio of 1:0.5:1.5 to obtain a filler; mixing 3 parts by mass of polyethyleneimine and 7 parts by mass of water under a nitrogen atmosphere to obtain a polyethyleneimine aqueous solution; mixing the polyethyleneimine aqueous solution and 1 part by mass of the filler, stirring at 62° C. for 9 hours, centrifuging and drying to obtain a modified filler.
[0039] Polyethyleneimine was purchased from GBK-PEI3 series from GPBK New Materials Technology (Shanghai) Co., Ltd.
[0040] The carboxylated double-walled carbon nanotubes have a diameter of 2-4 nm, a length of 0.5-2 μm, and a carboxyl content of 2.58 wt %. They were purchased from Xianfeng Nano, item number: 100227.
[0041] The diameter of carboxylated graphene oxide sheets is 0.5-5 micrometers and the thickness is 0.8-1.2 nm. They were purchased from Xianfeng Nano, item number: 100009.
[0042] The average size of carboxylated silica is 20 nm and it was purchased from Xianfeng Nano, item number: 103113.
[0043] The wetting agent is a mixture of Tween 60, Span 80 and Tween 80 in a mass ratio of 1:1.3:1.5.
[0044] The emulsifier is a mixture of peregal O, sodium dodecylbenzene sulfonate and a zwitterionic surfactant in a mass ratio of 1:0.5:1.6.
[0045] The preparation method of the zwitterionic surfactant comprises the following steps: S1: 13 parts by mass of 4-amino-3-hydroxybenzoic acid and 22 parts by mass of epichlorohydrin are dissolved in 55 parts by mass of ethanol, 5 parts by mass of 0.3 mol / L aqueous solution of sodium hydroxide are added, and the mixture is heated to 82° C. and reacted for 12 hours to obtain a product; S2: The product, 52 parts by mass of hexadecyldimethyl tertiary amine, 83 parts by mass of ethanol and 73 parts by mass of water were mixed, heated to 82° C., reacted for 26 hours, and the ethanol was removed by rotary evaporation to obtain a zwitterionic surfactant.
[0046] The antistatic agent is sorbitol.
[0047] The defoaming agent is TEGO901W defoaming agent.
[0048] The leveling agent is BYK300.
[0049] The dispersant is TEGODispers715w.
[0050] The preparation method of the microfiber spinning oil comprises the following steps: adding the modified filler, castor oil and No. 5 white oil into a reactor, controlling the temperature of the reactor to be 36°C, performing ultrasonic dispersion for 17 minutes, adding the remaining components, and stirring for 25 minutes to obtain the microfiber spinning oil.
[0051] Example 2 This embodiment provides a microfiber spinning oil, comprising the following components in parts by weight: 12 parts of castor oil, 3 parts of No. 5 white oil, 25 parts of polyurethane resin, 1 part of modified filler, 2 parts of antistatic agent, 6 parts of wetting agent, 4 parts of emulsifier, 1 part of defoamer, 1 part of leveling agent, 2 parts of dispersant, and 30 parts of deionized water; The preparation method of the polyurethane resin comprises the following steps: (1) adding a titanium tetrachloride aqueous solution to a benzoic acid aqueous solution in a volume ratio of 1:4, and stirring them uniformly to obtain a nano-titanium dioxide precursor solution, wherein the molar concentrations of the titanium tetrachloride aqueous solution and the benzoic acid aqueous solution are both 0.2 mol / L; (2) Weigh 4 parts by mass of diisocyanate, 1 part by mass of polyether polyol, and 10 parts by mass of butanone, mix well to obtain a mixed solution, add 5% by mass of nano-titanium dioxide precursor solution to the mixed solution, heat to 75°C, keep warm for 3 hours, continue to add 5 parts by mass of polyether polyol and 0.5 parts by mass of organic bismuth catalyst, react at 80°C for 4 hours, cool to 40°C, continue to add 4 parts by mass of 1,4-butanediol, 2 parts by mass of triethylamine and 5 parts by mass of deionized water, mix well, heat to 72°C, keep warm for 5 hours, and cool to room temperature to obtain a polyurethane resin.
[0052] The polyether polyol is a compound of polyether polyol A, polyether polyol B and polyether polyol C in a mass ratio of 0.2:1.3:1; wherein polyether polyol A is a polyether triol with a hydroxyl number of 535 mgKOH / g; polyether polyol B is a polyether diol with a hydroxyl number of 36-39 mgKOH / g; and polyether polyol C is a polyether diol with a hydroxyl number of 153-188KOH / g.
[0053] Polyether triol with hydroxyl number of 535 mgKOH / g, Arkema, France, model TO330. Polyether diol with hydroxyl number of 36-39 mgKOH / g, Xuzhou Yihuiyang New Materials Co., Ltd., DL-3000D. Polyether diol with hydroxyl number of 153-188KOH / g, Jining Tangyi Chemical Co., Ltd., HSH-310.
[0054] The organic bismuth catalyst was purchased from Shandong Xinghai Chemical Co., Ltd., model: organic bismuth catalyst LK-2.
[0055] The diisocyanate is isophorone diisocyanate.
[0056] The preparation method of the modified filler comprises the following steps: mixing carboxylated double-walled carbon nanotubes, carboxylated graphene oxide and carboxylated silicon dioxide in a mass ratio of 1:0.3:1.3 to obtain a filler; mixing 2 parts by mass of polyethyleneimine and 6 parts by mass of water under a nitrogen atmosphere to obtain a polyethyleneimine aqueous solution; mixing the polyethyleneimine aqueous solution and 1 part by mass of the filler, stirring at 60°C for 8 hours, centrifuging and drying to obtain a modified filler.
[0057] Polyethyleneimine was purchased from GBK-PEI3 series from GPBK New Materials Technology (Shanghai) Co., Ltd.
[0058] The carboxylated double-walled carbon nanotubes have a diameter of 2-4 nm, a length of 0.5-2 μm, and a carboxyl content of 2.58 wt %. They were purchased from Xianfeng Nano, item number: 100227.
[0059] The diameter of carboxylated graphene oxide sheets is 0.5-5 micrometers and the thickness is 0.8-1.2 nm. They were purchased from Xianfeng Nano, item number: 100009.
[0060] The average size of carboxylated silica is 20 nm and it was purchased from Xianfeng Nano, item number: 103113.
[0061] The wetting agent is a mixture of Tween 60, Span 80 and Tween 80 in a mass ratio of 1:1.2:1.5.
[0062] The emulsifier is a mixture of peregal O, sodium dodecylbenzene sulfonate and a zwitterionic surfactant in a mass ratio of 1:0.3:1.4.
[0063] The preparation method of the zwitterionic surfactant comprises the following steps: S1: Dissolve 12 parts by mass of 4-amino-3-hydroxybenzoic acid and 20 parts by mass of epichlorohydrin in 55 parts by mass of ethanol, add 4 parts by mass of 0.2 mol / L aqueous solution of sodium hydroxide, heat to 80° C., react for 10 hours, and obtain a product; S2: The product, 50 parts by mass of hexadecyldimethyl tertiary amine, 80 parts by mass of ethanol and 70 parts by mass of water were mixed, heated to 80° C., reacted for 25 hours, and the ethanol was removed by rotary evaporation to obtain a zwitterionic surfactant.
[0064] The antistatic agent is sorbitol.
[0065] The defoaming agent is TEGO901W defoaming agent.
[0066] The leveling agent is BYK300.
[0067] The dispersant is TEGODispers715w.
[0068] The preparation method of the microfiber spinning oil comprises the following steps: adding the modified filler, castor oil and No. 5 white oil into a reactor, controlling the temperature of the reactor to be 35° C., ultrasonically dispersing for 15 minutes, adding the remaining components, and stirring for 20 minutes to obtain the microfiber spinning oil.
[0069] Example 3 This embodiment provides a microfiber spinning oil, comprising the following components in parts by weight: 17 parts of castor oil, 8 parts of No. 5 white oil, 30 parts of polyurethane, 3 parts of modified filler, 5 parts of antistatic agent, 10 parts of wetting agent, 8 parts of emulsifier, 3 parts of defoamer, 3 parts of leveling agent, 5 parts of dispersant, and 36 parts of deionized water; The preparation method of the polyurethane resin comprises the following steps: (1) adding a titanium tetrachloride aqueous solution to a benzoic acid aqueous solution in a volume ratio of 1:6, stirring evenly, to obtain a nano-titanium dioxide precursor solution, wherein the molar concentrations of the titanium tetrachloride aqueous solution and the benzoic acid aqueous solution are both 0.5 mol / L; (2) Weigh 6 parts by mass of diisocyanate, 1 part by mass of polyether polyol, and 12 parts by mass of butanone, mix them evenly to obtain a mixed solution, add 10% by mass of nano-titanium dioxide precursor solution to the mixed solution, heat it to 80°C, keep it warm for 4 hours, continue to add 7 parts by mass of polyether polyol and 0.8 parts by mass of organic bismuth catalyst, react at 85°C for 6 hours, cool it to 45°C, continue to add 6 parts by mass of 1,4-butanediol, 4 parts by mass of triethylamine and 7 parts by mass of deionized water, mix them evenly, heat it to 76°C, keep it warm for 6 hours, and cool it to room temperature to obtain a polyurethane resin.
[0070] The polyether polyol is a compound of polyether polyol A, polyether polyol B and polyether polyol C in a mass ratio of 0.5:1.5:1; wherein polyether polyol A is a polyether triol with a hydroxyl number of 535 mgKOH / g; polyether polyol B is a polyether diol with a hydroxyl number of 36-39 mgKOH / g; and polyether polyol C is a polyether diol with a hydroxyl number of 153-188KOH / g.
[0071] Polyether triol with hydroxyl number of 535 mgKOH / g, Arkema, France, model TO330. Polyether diol with hydroxyl number of 36-39 mgKOH / g, Xuzhou Yihuiyang New Materials Co., Ltd., DL-3000D. Polyether diol with hydroxyl number of 153-188KOH / g, Jining Tangyi Chemical Co., Ltd., HSH-310.
[0072] The organic bismuth catalyst was purchased from Shandong Xinghai Chemical Co., Ltd., model: organic bismuth catalyst LK-2.
[0073] The diisocyanate is hexamethylene diisocyanate.
[0074] The preparation method of the modified filler comprises the following steps: mixing carboxylated double-walled carbon nanotubes, carboxylated graphene oxide and carboxylated silicon dioxide in a mass ratio of 1:0.6:1.6 to obtain a filler; mixing 4 parts by mass of polyethyleneimine and 8 parts by mass of water under a nitrogen atmosphere to obtain a polyethyleneimine aqueous solution; mixing the polyethyleneimine aqueous solution and 1 part by mass of the filler, stirring at 65° C. for 10 hours, centrifuging and drying to obtain a modified filler.
[0075] Polyethyleneimine was purchased from GBK-PEI3 series from GPBK New Materials Technology (Shanghai) Co., Ltd.
[0076] The carboxylated double-walled carbon nanotubes have a diameter of 2-4 nm, a length of 0.5-2 μm, and a carboxyl content of 2.58 wt %. They were purchased from Xianfeng Nano, item number: 100227.
[0077] The diameter of carboxylated graphene oxide sheets is 0.5-5 micrometers and the thickness is 0.8-1.2 nm. They were purchased from Xianfeng Nano, item number: 100009.
[0078] The average size of carboxylated silica is 20 nm and it was purchased from Xianfeng Nano, item number: 103113.
[0079] The wetting agent is a mixture of Tween 60, Span 80 and Tween 80 in a mass ratio of 1:1.4:1.7.
[0080] The emulsifier is a mixture of peregal O, sodium dodecylbenzene sulfonate and a zwitterionic surfactant in a mass ratio of 1:0.6:1.7.
[0081] The preparation method of the zwitterionic surfactant comprises the following steps: S1: 14 parts by mass of 4-amino-3-hydroxybenzoic acid and 23 parts by mass of epichlorohydrin are dissolved in 55 parts by mass of ethanol, 6 parts by mass of 0.4 mol / L aqueous solution of sodium hydroxide are added, and the mixture is heated to 85° C. and reacted for 15 hours to obtain a product; S2: The product, 55 parts by mass of hexadecyldimethyl tertiary amine, 85 parts by mass of ethanol and 75 parts by mass of water were mixed, heated to 85° C., reacted for 30 hours, and the ethanol was removed by rotary evaporation to obtain a zwitterionic surfactant.
[0082] The antistatic agent is sorbitol.
[0083] The defoaming agent is TEGO901W defoaming agent.
[0084] The leveling agent is BYK300.
[0085] The dispersant is TEGODispers715w.
[0086] The preparation method of the microfiber spinning oil comprises the following steps: adding the modified filler, castor oil and No. 5 white oil into a reactor, controlling the temperature of the reactor to be 38° C., ultrasonically dispersing for 20 minutes, adding the remaining components, and stirring for 30 minutes to obtain the microfiber spinning oil.
[0087] Comparative Example 1 The difference between this comparative example and Example 1 is that the polyether polyol is a compound of polyether polyol A, polyether polyol B and polyether polyol C in a mass ratio of 1:1:1.
[0088] Comparative Example 2 The difference between this comparative example and Example 1 is that carboxylated double-walled carbon nanotubes, carboxylated graphene oxide and carboxylated silicon dioxide are mixed in a mass ratio of 1:1:1 to obtain a filler.
[0089] Comparative Example 3 The difference between this comparative example and Example 1 is that the diameter of the carboxylated double-walled carbon nanotube is 10-20 nm, the length is 0.5-2 μm, and the carboxyl content is 2 wt%. It is purchased from Xianfeng Nano, item number: 100262. The average size of the carboxylated silicon dioxide is 100 nm. It is purchased from Xianfeng Nano, item number: 103114. The carboxylated graphene oxide is replaced by graphene oxide, the graphene oxide sheet diameter is 0.5-5 μm, the thickness is: 0.8-1.2 nm, purchased from Xianfeng Nano, item number: 100602.
[0090] Comparative Example 4 The difference between this comparative example and Example 1 is that the emulsifier is a mixture of peregal O, sodium dodecylbenzene sulfonate and a zwitterionic surfactant in a mass ratio of 1:1:1.
[0091] The preparation method of the zwitterionic surfactant comprises the following steps: S1: Dissolve 12 parts by mass of 4-amino-3-hydroxybenzoic acid and 20 parts by mass of epichlorohydrin in 55 parts by mass of ethanol, add 4 parts by mass of 0.2 mol / L aqueous solution of sodium hydroxide, heat to 80° C., react for 10 hours, and obtain a product; S2: The product, 50 parts by mass of hexadecyldimethyl tertiary amine, 80 parts by mass of ethanol and 70 parts by mass of water were mixed, heated to 80° C., reacted for 25 hours, and the ethanol was removed by rotary evaporation to obtain a zwitterionic surfactant.
[0092] Comparative Example 5 The difference between this comparative example and Example 1 is that the emulsifier is a mixture of peregal O, sodium dodecylbenzene sulfonate and isomeric decanol polyoxyethylene ether in a mass ratio of 1:0.3:1.4. Isomeric decanol polyoxyethylene ether is purchased from Lianhong Chemical, model: IP1007.
[0093] Comparative Example 6 The difference between this comparative example and Example 1 is that the emulsifier is a mixture of Tween 60, Span 80 and zwitterionic surfactant in a mass ratio of 1:0.3:1.4.
[0094] The preparation method of the zwitterionic surfactant comprises the following steps: S1: Dissolve 12 parts by mass of 4-amino-3-hydroxybenzoic acid and 20 parts by mass of epichlorohydrin in 55 parts by mass of ethanol, add 4 parts by mass of 0.2 mol / L aqueous solution of sodium hydroxide, heat to 80° C., react for 10 hours, and obtain a product; S2: The product, 50 parts by mass of hexadecyldimethyl tertiary amine, 80 parts by mass of ethanol and 70 parts by mass of water were mixed, heated to 80° C., reacted for 25 hours, and the ethanol was removed by rotary evaporation to obtain a zwitterionic surfactant.
[0095] Comparative Example 7 The difference between this comparative example and Example 1 is that the polyurethane resin is commercially available and purchased from Qingdao Ruikos New Material Technology Co., Ltd. with the product number FS-WPU.
[0096] Comparative Example 8 The difference between this comparative example and Example 1 is that the polyether polyol is commercially available and purchased from Guangzhou Qixu Chemical Co., Ltd. Model: MN-700.
[0097] Performance Testing The microfiber spinning oil prepared in Examples 1-3 and Comparative Examples 1-8 was sprayed onto the surface of nylon fiber (0.4 dtex) formed by melt spinning process by using an oil nozzle. The fibers were drawn (wherein the frequency of one roller was set to 60 Hz, the frequency of two rollers was set to 75 Hz, the frequency of three rollers was set to 78 Hz, the frequency of four rollers was set to 70 Hz, and the winding frequency was set to 65 Hz) and wound to obtain spun fibers.
[0098] Among them, the melt spinning machine is selected from the FCF-9 spinning machine produced by Linzi Fangchen Masterbatch Factory in Zibo City. The specific parameters are as follows: the setting temperatures of the five heating zones of the screw are 280℃, 290℃, 290℃, 280℃, and 280℃ respectively, the die head temperature is 280℃, the temperatures of the first roller, the second roller, the third roller, and the fourth roller are 65℃, 95℃, 95℃, and 95℃ respectively, and the measured blowing temperature is 10℃.
[0099] (1) Elongation test The tension of the spun fiber was twisted from 0.05 cN / dtex to 0.1 cN / dtex, and then the elongation of the twisted spun fiber was tested using an Instron (model-11127) electronic universal testing machine to test the elongation when the tensile strength was 1 cN / dtex.
[0100] (2) Tensile properties test The spun fibers were sampled according to GB / T14344-2003 standard. The samples were tested at room temperature using an Instron (model-11127) electronic universal testing machine to measure the breaking strength of the spun fibers.
[0101] (3) Anti-ultraviolet performance test The test was conducted in accordance with GB / T18830-209 "Evaluation of UV protection performance of textiles". The spun fibers were placed in a household washing machine, washed at 40°C for 30 minutes, dried, and then washed again. The washing-drying operation was repeated 6 times a day for 50 consecutive days, and the UV protection performance was tested again.
[0102] (4) The spinning oils prepared in Examples 1-3 and Comparative Examples 1-8 were sealed and stored at room temperature (25° C.) for 1 year to observe whether the spinning oils showed stratification and precipitation. If no stratification and / or precipitation occurred, it was recorded as passed; otherwise, it was recorded as failed.
[0103] The results are shown in Table 1; It can be seen from the above performance test results that the spinning oils of Examples 1-3 have a good effect on improving the performance of ultrafine fibers, especially the comprehensive performance of Example 1 is the most outstanding, which is mainly due to the synergistic compounding of multiple components.
[0104] The comparative examples, however, were not equipped with the necessary technical solutions, which resulted in the corresponding performance tests being significantly worse than those of the embodiments. In comparative examples 1, 7, and 8, the polyurethane preparation solutions were changed, and it can be seen that the weather resistance of the spinning oil decreased after washing. In comparative examples 2-3, the modified filler solution was not used, and the results showed that the breaking strength and elongation of the product were affected. In comparative examples 4-6, the emulsifier solution was changed, and the storage stability of the spinning oil was improved. The above experimental results further prove the importance of the technical solution defined in the present invention for its technical effects.
[0105] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A microfiber spinning oil, characterized in that: The invention comprises the following components in parts by weight: 12-17 parts of castor oil, 3-8 parts of white oil, 25-30 parts of polyurethane resin, 1-3 parts of modified filler, 2-5 parts of antistatic agent, 6-10 parts of wetting agent, 4-8 parts of emulsifier, 1-3 parts of defoaming agent, 1-3 parts of leveling agent, 2-5 parts of dispersant and 30-36 parts of deionized water; The preparation method of the polyurethane resin comprises the following steps: (1) adding a titanium tetrachloride aqueous solution to a benzoic acid aqueous solution in a volume ratio of 1:(4-6), stirring evenly, to obtain a nano-titanium dioxide precursor solution, wherein the molar concentrations of the titanium tetrachloride aqueous solution and the benzoic acid aqueous solution are both 0.2-0.5 mol / L; (2) Weigh 4-6 parts by weight of diisocyanate, 1 part by weight of polyether polyol, and 10-12 parts by weight of butanone, mix well to obtain a mixed solution, add 5-10% by weight of nano-titanium dioxide precursor solution to the mixed solution, heat to 75-80°C, keep warm for 3-4 hours, continue to add 5-7 parts by weight of polyether polyol and 0.5-0.8 parts by weight of organic bismuth catalyst, react at 80-85°C for 4-6 hours, cool to 40-45°C, continue to add 4-6 parts by weight of 1,4-butanediol, 2-4 parts by weight of triethylamine and 5-7 parts by weight of deionized water, mix well, heat to 72-76°C, keep warm for 5-6 hours, and cool to room temperature to obtain a polyurethane resin.
2. The microfiber spinning oil according to claim 1, characterized in that: The polyether polyol is a compound of polyether polyol A, polyether polyol B and polyether polyol C in a mass ratio of (0.2-0.5):(1.3-1.5):1; wherein polyether polyol A is a polyether triol having a hydroxyl number of 535 mgKOH / g; polyether polyol B is a polyether diol having a hydroxyl number of 36-39 mgKOH / g; and polyether polyol C is a polyether diol having a hydroxyl number of 153-188KOH / g.
3. The microfiber spinning oil according to claim 1, characterized in that: The diisocyanate is selected from one or more of toluene diisocyanate, isophorone diisocyanate and hexamethylene diisocyanate.
4. The microfiber spinning oil according to claim 1, characterized in that: The preparation method of the modified filler comprises the following steps: (1) mixing carboxylated double-walled carbon nanotubes, carboxylated graphene oxide and carboxylated silicon dioxide in a mass ratio of 1: (0.3-0.6): (1.3-1.6) to obtain a filler; (2) Under a nitrogen atmosphere, 2-4 parts by mass of polyethyleneimine and 6-8 parts by mass of water are mixed to obtain a polyethyleneimine aqueous solution, and the polyethyleneimine aqueous solution is mixed with 1 part by mass of a filler, stirred at 60-65° C. for 8-10 hours, centrifuged, and dried to obtain a modified filler.
5. The microfiber spinning oil according to claim 1, characterized in that: The wetting agent is a mixture of Tween 60, Span 80 and Tween 80 in a mass ratio of 1: (1.2-1.4): (1.5-1.7).
6. The microfiber spinning oil according to claim 1, characterized in that: The emulsifier is a mixture of peregal O, sodium dodecylbenzene sulfonate and zwitterionic surfactant in a mass ratio of 1: (0.3-0.6): (1.4-1.7); The preparation method of the zwitterionic surfactant comprises the following steps: S1: dissolving 12-14 parts by weight of 4-amino-3-hydroxybenzoic acid and 20-23 parts by weight of epichlorohydrin in 55 parts by weight of ethanol, adding 4-6 parts by weight of a 0.2-0.4 mol / L aqueous solution of sodium hydroxide, heating to 80-85° C., reacting for 10-15 hours, and obtaining a product; S2: Mix the product obtained in S1, 50-55 parts by mass of hexadecyldimethyl tertiary amine, 80-85 parts by mass of ethanol and 70-75 parts by mass of water, heat to 80-85° C., react for 25-30 hours, and remove ethanol by rotary evaporation to obtain a zwitterionic surfactant.
7. The microfiber spinning oil according to claim 1, characterized in that: The defoaming agent is selected from one or more of TEGO901W defoaming agent, TEGO902W defoaming agent, TEGO801W defoaming agent and TEGO810W defoaming agent.
8. The microfiber spinning oil according to claim 1, characterized in that: The leveling agent is selected from one or more of BYK300, BYK306 and BYK333.
9. The microfiber spinning oil according to claim 1, characterized in that: The dispersant is selected from one or more of TEGODispers715w, TEGODispers755w, and TEGOWet280.
10. A method for preparing the microfiber spinning oil according to any one of claims 1 to 9, characterized in that: The preparation method comprises the following steps: adding the modified filler, castor oil and white oil into a reaction kettle, controlling the temperature of the reaction kettle to be 35-38°C, ultrasonically dispersing for 15-20 minutes, adding the remaining components, stirring for 20-30 minutes, and obtaining the ultra-fine fiber spinning oil.
Citation Information
Cited By
Preparation method of anti-ultraviolet weather-resistant water-based paint
CN120536034A